2013
DOI: 10.1128/jcm.00284-13
|View full text |Cite
|
Sign up to set email alerts
|

A Novel High-Resolution Melt PCR Assay Discriminates Anaplasma phagocytophilum and “Candidatus Neoehrlichia mikurensis”

Abstract: f "Candidatus Neoehrlichia mikurensis" (Anaplasmataceae) is an emerging pathogen transmitted by Ixodes ticks. Conventional PCR and the newly developed high-resolution melt PCR were used to detect and discriminate "Candidatus Neoehrlichia mikurensis" and Anaplasma phagocytophilum. Both bacterial species were frequently found in Ixodes ricinus and Ixodes hexagonus but virtually absent from Dermacentor reticulatus. In rodents, "Candidatus N. mikurensis" was significantly more prevalent than A. phagocytophilum, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 22 publications
4
47
0
2
Order By: Relevance
“…Studies on the prevalence of C. Neoehrlichia mikurensis in ticks removed from people in The Netherlands [59] and Germany [28] have estimated that every ninth to 12th tick bite represents a risk of transmission of C. Neoehrlichia mikurensis, although the risk of becoming infected is likely to be considerably lower [59]. Infected ticks and rodents have been found in the vicinity of large cities, such as Berlin, Budapest, Guangzhou, Leipzig, and Zurich, indicating that large populations may be exposed to this new infectious agent [6,24,30,31,36,60].…”
Section: Vectors Reservoirs and Transmissionmentioning
confidence: 97%
See 3 more Smart Citations
“…Studies on the prevalence of C. Neoehrlichia mikurensis in ticks removed from people in The Netherlands [59] and Germany [28] have estimated that every ninth to 12th tick bite represents a risk of transmission of C. Neoehrlichia mikurensis, although the risk of becoming infected is likely to be considerably lower [59]. Infected ticks and rodents have been found in the vicinity of large cities, such as Berlin, Budapest, Guangzhou, Leipzig, and Zurich, indicating that large populations may be exposed to this new infectious agent [6,24,30,31,36,60].…”
Section: Vectors Reservoirs and Transmissionmentioning
confidence: 97%
“…Until 2014, C. Neoehrlichia mikurensis had not been found in the larval stage of ticks [43], and it had been inferred that it is not transmitted transovarially [30]. However, it was recently reported that four of ten larvae sampled in Austria were …”
Section: Vectors Reservoirs and Transmissionmentioning
confidence: 98%
See 2 more Smart Citations
“…The protocol used for this PCR was previously described by Krücken et al (2013). Briefly, reaction tubes contained 0.3 mM dNTPs, 0.3 µM of each primer, 0.1 U/µl Phusion Hot Start II High-Fidelity DNA Polymerase and 2 µl template DNA (20 -100 ng/µl) in 25 µl 1 × EvaGreen® Fluorescent DNA Stain (Jena Bioscience, Germany), 1 × Phusion HF buffer.…”
Section: Pcr Protocolsmentioning
confidence: 99%